2018
DOI: 10.1155/2018/2305062
|View full text |Cite
|
Sign up to set email alerts
|

Status of Artemisinin Resistance in Malaria Parasite Plasmodium falciparum from Molecular Analyses of the Kelch13 Gene in Southwestern Nigeria

Abstract: Evolution and spread of malaria parasite Plasmodium falciparum capable of evading antimalarials are the prime concern to malaria control. The currently effective drug, artemisinin (ART), is under threat due to detection of ART-resistant P. falciparum parasites in the Southeast Asian countries. It has been shown that amino acid (AA) mutations at the P. falciparum Kelch13 (Pfk13) gene provide resistance to ART. Nigeria, a part of the Sub-Saharan Africa, is highly endemic to malaria, contributing quite significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 16 publications
4
39
1
Order By: Relevance
“…In the present study, k13 propeller sequence analysis of P. falciparum parasites from different malaria-endemic areas in East Africa, Indian sub-continent and West & Central Africa did not detect the predicted artemisinin-resistant genotypes, but we observed only one non-synonymous mutation at codon G453A in a Kenyan isolate. Although antimalarial drug resistance originates from the greater Mekong subregion and subsequently spread worldwide, still we do not have any functional mutation from sub-Saharan Africa [48][49][50]. No mutations in PfATPase6 were found in the current study, which is in agreement with previous reports from India and Africa, where PfATPase6 polymorphisms rarely reported [51][52][53][54][55].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, k13 propeller sequence analysis of P. falciparum parasites from different malaria-endemic areas in East Africa, Indian sub-continent and West & Central Africa did not detect the predicted artemisinin-resistant genotypes, but we observed only one non-synonymous mutation at codon G453A in a Kenyan isolate. Although antimalarial drug resistance originates from the greater Mekong subregion and subsequently spread worldwide, still we do not have any functional mutation from sub-Saharan Africa [48][49][50]. No mutations in PfATPase6 were found in the current study, which is in agreement with previous reports from India and Africa, where PfATPase6 polymorphisms rarely reported [51][52][53][54][55].…”
Section: Discussionsupporting
confidence: 91%
“…The dynamics of resistance and its emergence are likely to be complex, particularly due to the interactions specific to each world (sub) region [28]. Similar studies in Cameroon and Nigeria have shown large differences according to region and time period, which makes it difficult to determine the spatio-temporal dynamics on polymorphism [29,30]. Some countries in this African subregion (Congo, Gabon, and DRC) have revealed the presence of parasites polymorphic for the A578S allele, others have detected novel alleles and still others, particularly in Benin, have not detected any polymorphism [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…Successful PCR products showing single band in gel were then subjected to PCR purification (using Fast AP alkaline phosphatise and exonuclease I) and further processed for DNA sequencing by Sanger methods (an in-house facility of ICMR-NIRTH, Jabalpur) with 2x coverage (sequenced from both the forward and reverse directions). Briefly, the amplified fragments were sequenced using Big Dye Terminator cycle sequencing ready reaction version 3.1 and ABI Prism DNA sequence Analyzer3130 [17,20]. For each isolate, sequence chromatograms were viewed carefully, and all the sequences from a single population were aligned (with the help of Gene Doc multiple Sequence Alignment Editor and shading utility version 2.7.000) alongside the reference Pfkelch13 sequence.…”
Section: Study Area Sample and Demographic Data Collectionmentioning
confidence: 99%
“…Further continuous reuse of this single ACT resulting in P. falciparum-resistant alleles to Artemisinin or its derivatives has been reported for the first time in Western Cambodia and Thailand border [2,3]; more interestingly, these resistant isolates might be carried by the parasites distributed rapidly across all SE Asian countries and also some parts of Africa [4,5]. Both Artemisinin Combination Therapies (ACTs) and its derivatives along with partner drug resis-tance to P. falciparum isolates have threatened the current efforts for the reduction of the burden of infectious malaria all over the world [6,7] As per the WHO guidelines, the definition of the emerged resistant alleles across Thai and Cambodia border has been characterized by [8,9] not only with reduced parasite clearance rate and increasing parasite clearance halflife or survived young ring stage parasites but also with the continuation of parasites on the third day of ACTs [1,[10][11][12][13][14][15][16][17][18]. These worldwide problems give rise to several approaches for the intense surveillance and detection of Artemisinin-resistant falciparum parasites including molecular marker evaluation [7,19].…”
Section: Introductionmentioning
confidence: 99%